FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN KONTRASEPSI IUD DI KLINIK BERSALIN BUDI MULIA MEDIKA PALEMBANG TAHUN 2013 - Tirta Anggraini Tirta Anggraini (STIKes Budi Mulia Sriwijaya, 2014)
ABSTRACT [Indonesia is the country with the largest population among the member countries of ASEAN (Association of Southeast Asian Nations) with a population of more 243.3 million. In Indonesia as many as the number of participants IUD KB 3933611 (11.12%). In South Sumatra planning acceptors IUD 56 027 (4.36%). In Palembang in 2011 the number of participants KB IUD 6,971 (4.44%). At the Maternity Clinic Budi Mulia Medika Palembang in 2012 the number of participants KB IUD 105 (18.6%). The purpose of this study is be knew the factors associated with the use of IUD Contraception in Maternity Clinic Budi Mulia Medika Palembang in 2013. This study uses the Analytic Survey cross-sectional approach. The population in this study were all active acceptors who visit to get family planning services at the Maternity Clinic Budi Mulia Medika Palembang in May - June 2013, earned a total of 32 respondents. Sampling was carried out by the technique of